Changes in brain structure and function during early aging in patients with chronic low back pain - Zu, Yao; Zhang, Zhou; Hao, Zengming; Jiang, Zimu; Chen, Ke; Wang, Yu; Zou, Changcheng; Ge, Le; Yu, Qiuhua; Zheng, Fuming; Wang, Chuhuai (Frontiers in Aging Neuroscience, 2024)
Objective: To explore the structural and functional changes in cognition-related brain regions in patients with chronic low back pain (CLBP) at earlier ages, and explore the impact of the interaction between CLBP and age on the brain. Methods: Seventy-six patients with CLBP were recruited and divided into "younger" age group (20-29 years, YA), "middle" age group (30-39 years, MA), and "older" age group (40-49 years, OA). All patients underwent functional magnetic resonance imaging (fMRI) as well as clinical psychological and pain-related symptoms assessments. Results: Structural analysis showed that patients in OA group had lower gray matter (GM) volumes in the orbitofrontal cortex (OFC) bilaterally and the right superior frontal gyrus (SFG) compared to YA group. The resting-state brain activity analysis showed that amplitude of low-frequency fluctuation (ALFF) values in the bilateral postcentral gyrus and left ventral medial prefrontal cortex (mPFC) were significantly different in the OA group. The functional connectivity (FC) in the right ventral dorsolateral prefrontal cortex (DLPFC) and the right insula was significantly decreased in the OA group compared to the YA and MA groups. Likewise, the FC in the left caudal parahippocampal gyrus (PHG) and left inferior parietal lobule (IPL) were significantly lower in the MA and OA groups compared to the YA group. In addition, both the structural properties and the FC values of these brain regions were significantly correlated with age. Conclusion: This preliminary study concludes that CLBP affects the aging process. The synergistic effects of CLBP and aging accelerate the functional and structural decline of certain areas of the brain, which not only affects pain processing, but are also may be associated with cognitive declines.